Business Cycle in Czechoslovakia Under Central Planning : Were Credit Shocks Causing it? - Bulir, Ales (IMF Working Papers; Working Paper ;, 1996)
This paper examines credit origins of the business cycle in the former Czechoslovakia. Industrial production is found to be cointegrated with various measures of bank credit during 1976-90 and it is shown that noninvestment credits are Granger-causing industrial production and that a feedback relation exists between investment credits and industrial production. Although the potency of credit supply shocks to industrial production has been changing, production decline (growth) seems to follow credit tightening (loosening). However, the paper confirms that credit shocks were only a minor part of the output decline in 1989-90.